Valuation and Volatility of Virtual Properties in Metaverse: Exploring New Market Opportunities and Speculative Dynamics Based on Decentraland - Dawid Narowski; Celso Santos; Lukasz Borowski; Michal Apollo; Kamil Maciuk (Journal of Metaverse)
Existing reality has been repeatedly subjected to multifaceted and multidimensional analyses. However, alongside it, a virtual reality exists, populated with virtual art, objects in games, cyber-pets, and virtual properties, collectively worth billions of real dollars. This virtual reality is associated with the concept of the 'metaverse' (a term derived from 'meta' and 'universe'), signifying a space that facilitates life in a virtual world. This space has a quantifiable value and is traded on specially designed platforms. The study focuses on the largest of these platforms, Decentraland, where users can purchase virtual properties using a cryptocurrency called MANA. Based on an analysis of 207 property transactions, the study examines whether these properties can be appraised using typical approaches applicable to “real” properties. It explores the relationship between spatial attributes, property price, and price volatility over time, calculating correlation coefficients for this purpose. Additionally, the study investigates the number of property sales, including multiple sales, and the proportion of properties with ITEMs on them, determining the correlation coefficients between price and parcel attributes. This study is the first to accomplish what researchers in the real estate market have long been doing. The results distinctly show that the virtual real estate market is governed by different factors compared to the traditional market, with property price and location remaining as two crucial aspects in the decision-making process for purchasing a property.